Lung and Heart Injury in a Nonhuman Primate Model of Partial-body Irradiation with Minimal Bone Marrow Sparing: Histopathological Evidence of Lung and Heart Injury. Issue 3 (March 2019) - Parker, George A.; Li, Na; Takayama, Kyle; Farese, Ann M.; MacVittie, Thomas J.
Abstract : Abstract: Male rhesus macaques were subjected to partial-body irradiation at 10, 11, or 12 Gy with 5% bone marrow protection. Animals were euthanized when dictated by prospectively determined clinical parameters or at approximately 180 d following irradiation. Histological sections of lung and heart were stained with hematoxylin and eosin as well as a battery of histochemical and immunohistochemical stains. Histopathological alterations in the lung were centered on fibrosis, inflammation, and reactive/proliferative changes in pneumocytes. These changes were noted in animals necropsied after approximately 85–100 d postirradiation and extending through the observation period. Interstitial and pleural fibrosis demonstrated by Masson's trichrome staining were associated with increased alpha smooth muscle actin and collagen 1 immunohistochemical staining. Areas of interstitial fibrosis had reduced microvascular density with CD31 immunohistochemical staining. Accumulations of CD163- and CD206-positive alveolar macrophages were present in areas of interstitial fibrosis. Unidentified cells termed "myxoid" cells in alveolar walls had histochemical and immunohistochemical staining characteristics of epithelial-, endothelial-, or pericyte-mesenchymal transition states that were developing myofibroblast features. Distinctive focal or multifocal alveolar-bronchiolar hyperplasia had microscopic features of preneoplastic proliferation. Delayed radiation-associated changes in the heart consisted primarily of myocardial fibrosis, with rare histological evidence of myofiber degeneration.